Astrocyte-derived TNF and glutamate critically modulate microglia activation by methamphetamine - Canedo, Teresa (2021)
Methamphetamine (Meth) is a powerful illicit psychostimulant, widely used for recreational purposes. Besides disrupting the monoaminergic system and promoting oxidative brain damage, Meth also causes neuroinflammation, contributing to synaptic dysfunction and behavioral deficits. Aberrant activation of microglia, the largest myeloid cell population in the brain, is a common feature in neurological disorders triggered by neuroinflammation. In this study, we investigated the mechanisms underlying the aberrant activation of microglia elicited by Meth in the adult mouse brain. We found that binge Meth exposure caused microgliosis and disrupted risk assessment behavior (a feature that usually occurs in individuals who abuse Meth), both of which required astrocyte-to-microglia crosstalk. Mechanistically, Meth triggered a detrimental increase of glutamate exocytosis from astrocytes (in a process dependent on TNF production and calcium mobilization), promoting microglial expansion and reactivity. Ablating TNF production, or suppressing astrocytic calcium mobilization, prevented Meth-elicited microglia reactivity and re-established risk assessment behavior as tested by elevated plus maze (EPM). Overall, our data indicate that glial crosstalk is critical to relay alterations caused by acute Meth exposure.